ReView: a new approach to peer review, using WordPress - Bazargan, Kaveh (Septentrio Conference Series, 2014)
The most requirements for a peer review system are a robust database, and comprehensive and secure control of user roles. Traditionally, peer review systems have been written from the ground up, requiring substantial manpower. We have found that using WordPress as the foundation of the system can result in a surprisingly flexible PR system with a user-friendly interface. By incorporating modified versions of available plugins, it is possible to incorporate unconventional functionality, e.g. a social network module.